Relationship Between Job Satisfaction and Affective Commitment in Kindergarten Teachers: Hubungan Antara Kepuasan Kerja dengan Komitmen Afektif pada Guru Taman Kanak-Kanak - Jannah, Ashhabul; Widyastuti, Widyastuti (Indonesian Journal of Innovation Studies, 2023)
This research is motivated by the phenomenon of teachers with problems related to job satisfaction and commitment to their workplace. This study aims to determine the relationship between Job Satisfaction and Affective Commitment to Aisyiyah Kindergarten Teachers in Candi Sidoarjo District. This research is a quantitative research with a correlational approach. The variables used are Job Satisfaction and Affective Commitment. The number of research samples was 63 teachers and the sampling technique used was the non-probability sampling technique. The data collection technique used the Job Satisfaction scale (α = 0.939) and the Affective Commitment scale (α = 0.964). The data analysis technique uses Pearson's product moment correlation with the help of SPSS 17.0. The results of the research analysis show that the correlation coefficient (rxy) = 0.453 with a significance of 0.000 <0.05, which means that there is a significant positive relationship between job satisfaction and affective commitment to Aisyiyah Kindergarten teachers in Candi Sidoarjo district. The effect of job satisfaction on affective commitment is 20.5%.